Kajian Teknis Penentuan Geometri Peledakan Untuk Mengoptimalisasikan Perolehan Hasil Peledakan CV. Tekad Jaya Desa Lareh Sago Halaban, Kabupaten Lima Puluh Kota, Sumatera Barat - Andre Tri Wahyudi; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract.Limestone Mining at CV. Tekad Jaya with a surface mining system with the Quarry mining method. The proportion of boulder-sized fragmentation blasting 80 cm produced at this time in the field is > 30%, as a result the diggability of the digging time is not optimal that is ±13 second. This study aims to design a new blasting geometry to obtain optimal fragmentation results that is <20%, so that the digging time results to be optimal that is 8-10 second. The recommendation of blasting geometry using the research method is based on the theory of R.L. Ash and C.J. Konya and from one of the good blasting geometry map designs will be applied in the field so as to get the optimal blasting geometry design from one of these blasting geometry designs to be applied in the future for the company. The basis of the results of field application of one of the blasting geometry plans, namely: load: 1.9 m, space: 1.9 m, stemming: 1.4 m, subdrilling: 0.3 m, level height: 5 m, hole depth explosion of 5.5 m, powder column: 4.1 m, and powder factor: 0.8 kg / m3 where the fragmentation of the boulder size 80 cm resulting from the split desktop software analysis was 3.17%. The resulting digging time was 9.63 seconds Keywords:Geometry Blasting, Blasting Result Fragmentation, R.L. Ash, C.J. Konya, Excavation Time